ADD SUBTRACT AND MULTIPLY LINEAR EXPRESSIONS

About "Add subtract and multiply linear expressions"

Add subtract and multiply linear expressions :

Whenever we want add or subtract linear expressions, we must know about combining like terms. 

Like terms or Similar terms: 

Like terms are the terms which have the same variables with same exponent for each variable.

Examples : 7x, 3x, - 4x

7x and -5xy are not like terms. Because in the first term we have the variable x only. But in the second term, we have x and y.So we cannot combine them.

To add or subtract linear expression, we have two methods

(i) Horizontal method

(ii) Vertical method

Horizontal method :

In this method, we arrange all the terms in a horizontal line and then add or subtract by combining the like terms.

Vertical method :

In this method, we should write the like terms vertically and then add or subtract.

Add subtract and multiply linear expressions - Examples

Let us look into some example problems to understand how to add subtract and multiply linear expressions.

Example 1 :

Add 6a + 3 and 4a - 2.

Solution :

Adding linear expressions in horizontal method :

  =   (6a + 3) + (4a - 2)

  =   6a + 4a + 3 - 2

  =  10a + 1

Adding linear expressions in vertical method :

Example 2 :

Add 5y + 8 + 3z and 4y - 5

Solution : 

Adding linear expressions in horizontal method :

  =   (5y + 8 + 3z) + (4y - 5)

  =   5y + 4y + 8 - 5 + 3z 

  =   9y + 3z + 3

Adding linear expressions in vertical method :

Example 3 :

Add 10x²- 5xy + 2y², -4x²+ 4xy + 5y², 3x²- 2xy - 6y²

Solution : 

Adding linear expressions in horizontal method :

  =   (10x²- 5xy + 2y²) + (-4x²+ 4xy + 5y²) + (3x²- 2xy - 6y²)

  =  10x² - 4x² + 3x² - 5xy + 4xy - 2xy + 2y²+ 5y² - 6y²

=  13x² - 4x² - 7xy + 4xy + 7y² - 6y²

=  9x² - 3xy + y² 

Adding linear expressions in vertical method :

Example 4 :

Subtract 6a - 3b from - 8a + 9b.

Solution : 

Subtracting linear expressions in horizontal method: 

  =   (- 8a + 9b) -  (6a - 3b)

Distribute the negative sign inside the parentheses 

  =   - 8a + 9b -  6a + 3b

=  -8a - 6a + 9b + 3b

=  -14a + 12b

Subtracting linear expressions in vertical method :

Example 5 :

Subtract a² + b² - 3ab from a² + b² - 3ab

Solution : 

Subtracting linear expressions in horizontal method: 

  =  (a² - b² - 3ab) - (a²+ b² - 3ab)

=  a² - b² - 3ab - a² - b² + 3ab

=  a² - a² - b² - b² - 3ab  + 3ab

=  - b² - b²

=  - 2b²

Subtracting linear expressions in vertical method :

Example 6 :

Multiply (3a - 2b) (2p + 3q)

Solution : 

By using distributive property we can multiply two polynomials.

  =  (3a - 2b) (2p + 3q)

  =  3a(2p + 3q) - 2b(2p + 3q)

  =  6ap + 9aq - 4pb - 6qb

Since there is not like terms, we cannot combine any more.

Hence the answer is 6ap + 9aq - 4pb - 6qb.

Example 7 :

Multiply (3x - 7) (7x - 3)

Solution : 

By using distributive property we can multiply two polynomials.

  =  (3x - 7) (7x - 3)

  =  3x(7x - 3) - 7(7x - 3)

  =  21x² - 9x - 49x + 21

=  21x² - 58x + 21

Hence the answer is  21x² - 58x + 21.

After having gone through the stuff given above, we hope that the students would have understood "Add subtract and multiply linear expressions"

Apart from the stuff given above, if you want to know more about "Add subtract and multiply linear expressions", please click here

Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here.

Widget is loading comments...